Linear transverse vibrations of a viscous magnetoelastic plate - Н. М. Эргашева; М. Х. Тешаев; З. И. Болтаев; М. З. Шарипов (Современные инновации, системы и технологии)
In this paper, linear transverse vibrations of a magnetoelastic plate are considered. The problem of forced vibrations of a magnetoelastic plate in a magnetic field is solved. Asymptotic and empirical frequency densities of linear transverse oscillations of the plate under the action of a magnetic field are found. Using the asymptotic method, solutions of the dynamic edge effect in transverse and longitudinal magnetic fields were obtained. To compare asymptotic estimates, studies and calculations were carried out using numerical modeling methods.